Workplace Victimization in the Public Sector: Evidence on Negative Affectivity and Conflict Styles - Joko Suyono (Sebelas Maret Business Review, 2019)
The purpose of the study is to analyze negative affectivity and conflict styles as potential causes of workplace victimization. A sample survey of 100 respondents was conducted in the public sector in Indonesia. Multiple regression analysis was used in the study to test the hypothesis. Results suggested that there was a significant relationship between negative affectivity and perceived victimization. Furthermore, we found that conflict styles were related to perceived victimization. Obliging style and integrating style had a negative relationship with perceived victimization. Meanwhile, the dominating style was positively related to perceived victimization. This study investigated empirically workplace victimization in the public sector from the victims’ perspective. Caution should be exercised in generalizing the results. Future studies can investigate both victims' and perpetrator's perspectives in the analysis of workplace victimization. Also, future research should pay attention to the extent to which certain types of leaders, organizational factors and person behaviors influence victimization. An understanding of individual determinants will help an organization to prevent victimization in the environment. Also, the organization should have a certain mechanism to protect employees from workplace victimization. To the extent of the author’s knowledge, this research is one of the few studies that has been made from the victim’s perspective of workplace victimization in the public sector in Indonesia.